2014
DOI: 10.1007/s00122-014-2417-5
|View full text |Cite
|
Sign up to set email alerts
|

A yield-associated gene TaCWI, in wheat: its function, selection and evolution in global breeding revealed by haplotype analysis

Abstract: Wheat anther-specific invertase genes were haplotyped in wheat. Strong allelic selection occurred during wheat polyploidization, domestication and breeding because of their association with yield traits. Plant invertase hydrolyzes sucrose into glucose and fructose. Cell wall invertase (CWI), one of the three types of invertase, is essential for plant development. Based on isolated TaCWI genes from chromosomes 4A, 5B and 5D, two SNPs were detected in the promoter region of TaCWI-4A, and four SNPs and two Indels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 39 publications
4
71
0
Order By: Relevance
“…In addition, the haplotype numbers of TaGW2-6A and TaGW2-6B decreased from diploids, to tetraploids and hexaploids (Figure 6 and Figure S5). Dramatic reductions in diversity in other genes, such as TaSUS1-7A, TaGS5-5A , and TaCWI , following polyploidization reported in other species (Hou et al, 2014; Jiang et al, 2015; Ma et al, 2016). All of these reports indicate that strong differentiation of important yield-related genes occurred during polyploidization and domestication of both tetraploid and hexaploid wheats.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, the haplotype numbers of TaGW2-6A and TaGW2-6B decreased from diploids, to tetraploids and hexaploids (Figure 6 and Figure S5). Dramatic reductions in diversity in other genes, such as TaSUS1-7A, TaGS5-5A , and TaCWI , following polyploidization reported in other species (Hou et al, 2014; Jiang et al, 2015; Ma et al, 2016). All of these reports indicate that strong differentiation of important yield-related genes occurred during polyploidization and domestication of both tetraploid and hexaploid wheats.…”
Section: Discussionmentioning
confidence: 92%
“…Examples include OsGS5, ZmGS3, ZmGW2-CHR4, TaTEF-7A , and TaCWI-4A (Li et al, 2010a,b, 2011; Zheng et al, 2014; Jiang et al, 2015). Previous studies (Su et al, 2011; Qin et al, 2014) also showed that genetic diversity mainly occurred in the promoter regions of TaGW2-6A and TaGW2-6B in common wheat.…”
Section: Discussionmentioning
confidence: 99%
“…Another yield-related wheat anther-specific invertase gene, TaCWI , encodes cell wall invertase (CWI), which hydrolyzes sucrose into glucose and fructose. Among several haplotypes tested, only one, TaCWI - 5D , was significantly associated with TKW (Jiang et al 2015). …”
Section: The Major Genes Of the Second Grmentioning
confidence: 99%
“…TaGW2 , encoding an E3 ubiquitin ligase and associated with GW and TGW, was cloned based on the homologous rice gene GW2 (Su et al, 2011). Similarly, TaCwi-A1 associated with TGW (Ma et al, 2012; Jiang et al, 2015), TaGASR7-A1 for GL and yield (Dong et al, 2014), TaGS-D1 for GL and TGW (Zhang et al, 2014), and TaTGW6 encoding an indole-3-acetic acid (IAA)-glucose hydrolase (Hu et al, 2016) have been cloned based on rice gene sequences.…”
Section: Introductionmentioning
confidence: 99%